SYSTEM MODEL FOR WEB-BASED TEACHER PERFORMANCE ASSESSMENT - Magdalena, Hilyah; Umami, Umami; Santoso, Hadi (Jurnal Transformatika, 2019)
The performance of teachers in educational institutions needs to have an appreciation and assessment that has a basis. Teacher performance assessment is one of the bases for decision making related to the career of the teacher. To improve the quality and accuracy of performance appraisal, this study designs a web-based teacher performance assessment decision support system. The Decision Support System method used is Analytical Hierarchy Process (AHP), and information system design uses the Object Oriented Analysis and Design (OOAD) method. Respondents in this study were deputy principals, teacher representatives, and committee representatives. The results of the calculation of the respondent questionnaire were carried out with a paired comparison matrix. The results of the combined calculation showed that the first level criteria which were the highest weighted were Social with a weight of 33.4% and the alternative teacher with the best performance was Vera Asmara with a value of 22.9%.
Keywords: Teacher Performance; DSS; AHP